Thermo-rheological responsive microcapsules for time-dependent controlled release of human mesenchymal stromal cells. (3rd October 2017) - Mak, W. C.; Magne, B.; Cheung, K. Y.; Atanasova, D.; Griffith, M.
Abstract : Injectable thermo-rheological responsive capsules for controlled release of hMSCs. Abstract : Human mesenchymal stromal cells (hMSCs) are adult-source cells that have been extensively evaluated for cell-based therapies. hMSCs delivered by intravascular injection have been reported to accumulate at the sites of injury to promote tissue repair and can also be employed as vectors for the delivery of therapeutic genes. However, the full potential of hMSCs remains limited as the cells are lost after injection due to anoikis and the adverse pathologic environment. Encapsulation of cells has been proposed as a means of increasing cell viability. However, controlling the release of therapeutic cells over time to target tissue still remains a challenge today. Here, we report the design and development of thermo-rheological responsive hydrogels that allow for precise, time dependent controlled-release of hMSCs. The encapsulated hMSCs retained good viability from 76% to 87% dependent upon the hydrogel compositions. We demonstrated the design of different blended hydrogel composites with modulated strength ( S parameter) and looseness of hydrogel networks ( N parameter) to control the release of hMSCs from thermo-responsive hydrogel capsules. We further showed the feasibility for controlled-release of encapsulated hMSCs within 3D matrix scaffolds. We reported for the first time by a systematic analysis that there is a direct correlation between the thermo-rheological properties associated with the degradation of the hydrogel composite and the cell release kinetics. This work therefore provides new insights into the further development of smart carrier systems for stem cell therapy.